A Firm's-Eye View of Policy and Fiscal Reforms in Cameroon - Gauthier, Bernard; Soloaga, Isidro; Tybout, James (World Bank, Washington, DC, 2015)
After decades of heavy trade restrictions, fiscal distortions, and currency overvaluation, Cameroon implemented important commercial and fiscal policy reforms. Almost simultaneously, a major CFA devaluation cut the international price of Cameroon's currency in half. The authors examine the effects of these reforms on the incentive structure that manufacturing firms face. Did they create a coherent set of new signals? Was the net effect to stimulate the production of tradable goods? Was the dispersion of tax burdens lessened? They address each of these questions using a cost function decomposition applied to detailed firm-level panel data. They observe that Cameroon's reforms appear to have sent clear new signals to manufacturers, as the effective rate of protection fell by between 80 and 120 percentage points. Unlike trade liberalization, neither tax reforms nor the CFA devaluation had a major systemic effect on profit margins. But the CFA devaluation did twist relative prices dramatically in favor of exportable goods, so export-oriented firms exhibited rapid output growth.